Diagnostic test accuracy of dipstick urinalysis for diagnosing urinary tract infection in febrile infants attending the emergency department. Issue 12 (24th August 2022) - Waterfield, Thomas; Foster, Steven; Platt, Rebecca; Barrett, Michael J; Durnin, Sheena; Maney, Julie-Ann; Roland, Damian; McFetridge, Lisa; Mitchell, Hannah; Umana, Etimbuk; Lyttle, Mark D
Abstract : Objective: To report the diagnostic test accuracy of dipstick urinalysis for the detection of urinary tract infections (UTIs) in febrile infants aged 90 days or less attending the emergency department (ED). Design: Retrospective cohort study. Patients: Febrile infants aged 90 days or less attending between 31 August 2018 and 1 September 2019. Main outcome measures: The sensitivity, specificity and predictive values of dipstick urinalysis in detecting UTIs defined as growth of ≥100 000 cfu/mL of a single organism and the presence of pyuria (>5 white blood cells per high-power field). Setting: Eight paediatric EDs in the UK/Ireland. Results: A total of 275 were included in the final analysis. There were 252 (92%) clean-catch urine samples and 23 (8%) were transurethral bladder catheter samples. The median age was 51 days (IQR 35–68.5, range 1–90), and there were 151/275 male participants (54.9%). In total, 38 (13.8%) participants had a confirmed UTI. The most sensitive individual dipstick test for UTI was the presence of leucocytes. Including 'trace' as positive resulted in a sensitivity of 0.87 (95% CI 0.69 to 0.94) and a specificity of 0.73 (95% CI 0.67 to 0.79). The most specific individual dipstick test for UTI was the presence of nitrites. Including trace as positive resulted in a specificity of 0.91 (95% CI 0.86 to 0.94) and a sensitivity of 0.42 (95% CI 0.26 to 0.59). Conclusion: Point-of-care urinalysis is moderately sensitive and highly specific for diagnosing UTI in febrile infants. The optimum cut-point to for excluding UTI was leucocytes (1+), and the optimum cut-point for confirming UTI was nitrites (trace). Trial registration number: NCT04196192 . Abstract : This retrospective cohort study aimed to assess the diagnostic test accuracy of dipstick urinalysis for the detection of urinary tract infections in febrile infants (<90 days) in the ED. The authors found that point-of-care urinalysis is moderately sensitive and highly specific for diagnosing UTI in this population.